Uganda : Background Paper on Issues in Financial Sector Reform, and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This Background Paper examines issues in Uganda's financial sector reform. In Uganda, reforms in the financial sector have included the liberalization of interest rates, the development of instruments of indirect monetary control, the modernization of banking legislation, the restructuring of the central bank, and reforms in the commercial banking system. These reforms are aimed at improving monetary management, which would enhance the prospects for achieving stabilization. Ultimately, financial sector reforms will contribute to long-term sustainable growth by mobilizing domestic savings and channeling these resources to the most profitable investment projects.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet